An investigation into the role of TMED1 in IL-33/ST2L singalling pathway - Connolly, Dympna (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
This thesis set out to characterise the GOLD domain containing protein, TMED1 which had been shown to associate with ST2L, the receptor for the cytokine IL-33 and to investigate its relationship with ST2L.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.